Organizational Communication: Approaches and Processes - Miller, Katherine (Wadsworth Cengage Learning, 2009)
ORGANIZATIONAL COMMUNICATION: APPROACHES AND PROCESSES, 5th Edition presents organizational communication from both a communication and managerial perspective. Professor Miller’s clear writing style and consistent use of examples and case studies result in a text that you’ll find easy to understand.